1988
DOI: 10.1037/0022-3514.55.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Personal goals and interpersonal support and hindrance as factors in psychological distress and well-being.

Abstract: This study examined psychological distress and well-being as a function of the characteristics of personal projects and project-relevant social support and social hindrance provided by the three most important people in subjects' lives. Three project factors (Project Mastery, Strain, and Self-Involvement) were found to account for significant variation in both psychological distress and well-being. Project support was generally found to be significantly related to well-being, but not to distress. However, proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
135
1
12

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 36 publications
17
135
1
12
Order By: Relevance
“…In contrast, negative emotions are formulated by the perception of unsuccessful goal pursuit which may result from insufficient agency thinking and / or pathway thinking or the ineffective ability to overcome the problem. These points were supported by respective researches (e.g., Snyder, Sympson, Ybasco, Borders, Babyak & Higgins, 1996;Stephanou, 2010), and are in agreement with findings for reported lessened well-being stern from perceived difficulties in pursuit of important goals (Diener, 1984;Ruehlman & Wolchik, 1988).…”
Section: Attributions and Emotions For Academic Achievementsupporting
confidence: 89%
“…In contrast, negative emotions are formulated by the perception of unsuccessful goal pursuit which may result from insufficient agency thinking and / or pathway thinking or the ineffective ability to overcome the problem. These points were supported by respective researches (e.g., Snyder, Sympson, Ybasco, Borders, Babyak & Higgins, 1996;Stephanou, 2010), and are in agreement with findings for reported lessened well-being stern from perceived difficulties in pursuit of important goals (Diener, 1984;Ruehlman & Wolchik, 1988).…”
Section: Attributions and Emotions For Academic Achievementsupporting
confidence: 89%
“…These studies include demographically diverse samples of respondents including college undergraduates (Ruehlman & Wolchik, 1988), recently bereaved or disabled older adults with matched control groups (Finch, Okun, Barrera, Zautra, & Reich, 1989;Okun, Melichar, & Hill, 1990), caregivers of Alzheimer's disease patients (Kiecolt-Glaser, Dyer, & Shuttleworth, 1988), and a representative community sample (Schuster, Kessler, & Aseltine, 1990). The results of these studies provide consistent support for the hypotheses.…”
mentioning
confidence: 65%
“…They found that personal resources contributed more to well-being if they matched each person's goals or personal strivings. Moreover, in an Australian study (Omodei & Wearing, 1990), involvement measured as flow experience (being absorbed in an activity) correlated strongly with having created something that had a sense of purpose and meaning, labelled need satisfaction (see also, Ruehlman & Wolchik, 1988). Hence, meaningful involvement should also be measured as a desire-priority.…”
Section: Meaningful Involvementmentioning
confidence: 99%
“…For example, when undergraduate students were asked to rate the three most importance persons in their lives, their parents dominated-before spouse, boyfriend or girlfriend (Ruehlman & Wolchik, 1988). In the same vein, Rodriguez, Mira, Myers, Morris and Cardoza (2003) found that support from their respondets'original family enhanced well-being.…”
Section: Contact With One's Original Familymentioning
confidence: 99%